PML promotes MHC class II gene expression by stabilizing the class II transactivator - Ulbricht, Tobias; Schmitt, Eberhard (The journal of cell biology, 2012)
Promyelocytic leukemia (PML) nuclear bodies selectively associate with transcriptionally active genomic regions, including the gene-rich major histocompatibility (MHC) locus. In this paper, we have explored potential links between PML and interferon (IFN)-γ-induced MHC class II expression. IFN-γ induced a substantial increase in the spatial proximity between PML bodies and the MHC class II gene cluster in different human cell types. Knockdown experiments show that PML is required for efficient IFN-γ-induced MHC II gene transcription through regulation of the class II transactivator (CIITA). PML mediates this function through protection of CIITA from proteasomal degradation. We also show that PML isoform II specifically forms a stable complex with CIITA at PML bodies. These observations establish PML as a coregulator of IFN-γ-induced MHC class II expression.